Planning and Scheduling Approaches in Humanitarian Projects: A Case of AVSI Foundation Somalia - Ayanle Nor, Arale (2023)
This thesis explores Planning and Scheduling Approaches in Humanitarian Projects, focusing on the AVSI Foundation's initiatives in Somalia. Humanitarian projects face numerous challenges, and AVSI encounters issues such as limited resources, political instability, security concerns, and unpredictable climate conditions. The study aims to identify these challenges and shed light on the planning and scheduling approaches employed by AVSI in Somalia. Qualitative methods, specifically interviews with individuals experienced in various AVSI projects were used to gather insights. The findings reveal that AVSI faces difficulties in planning and scheduling, particularly due to the mentioned challenges. Notably, AVSI employs diverse approaches, including the Participatory Planning Approach in health and education projects, Artificial Intelligence in complex projects, and a legal framework approach. Additionally, AVSI integrates various project management concepts such as Project Lifecycle, Work Breakdown Structure, Risk Management, Quality Management, Stakeholder Management, Monitoring and Evaluation, and Resource Management into its planning activities. This study contributes valuable insights into the practical application of planning and scheduling strategies in humanitarian projects, with implications for improving the effectiveness of AVSI Foundation's endeavors in Somalia.